HIGH PREVALENCE OF OSTEOCHONDRAL AND SOFT-TISSUE DAMAGE IN THE ANKLES OF ASYMPTOMATIC PROFESSIONAL SNOWBOARDERS: A PROSPECTIVE EVALUATION WITH 3T MRI. Issue 7 (11th March 2014) - Briggs, K; Ho, C; Ryan, W; Bower, G; Hackett, T; Clanton, T
Abstract : Background: Professional snowboarders are exposed to repetitive high-impact loading on a daily basis throughout their competitive and training careers. Objective: The purpose of this study was to determine the prevalence of ankle derangements on magnetic resonance imaging (MRI) in asymptomatic professional snowboarding athletes. We hypothesized that elite snowboarders with asymptomatic ankles would exhibit osteochondral and soft-tissue changes on 3T MRI. Design: Between February and March 2013, professional snowboarders specializing in various disciplines were recruited to participate in the study. 3T MRIs of each ankle were obtained prospectively. Setting: World Cup snowboarding competition. Participants: Each participant underwent a physical examination of each ankle and completed a short survey including demographic, pain, and functional questions prior to MRI evaluation to ensure that each of the included ankles were truly asymptomatic. Sixteen professional snowboarders (29 asymptomatic ankles) were included in the study. Risk factor assessment: A 3T MRI scan of each asymptomatic ankle was performed. Main outcome measurements: The MRI findings were recorded by an experienced musuloskeletal radiologist. Results: There were 9 males (16 ankles) and 7 females (13 ankles) with a mean age of 23.4 years (range, 18–31 years) who had been professional snowboarders for a median of 6.5 years (range, 2–15 years). It was found that all 29 ankles (100%) had notable derangements on 3T MRI scans including various ligamentous pathologies, tendinous pathologies, syndesmosis injuries, effusions, osteochondral injuries and bony edema. Increasing age and years of competitive snowboarding were significantly associated with chondral damage of the ankle (P=.017 and P=.026, respectively). Conclusion: All 29 asymptomatic ankles in this study had notable derangements on MRI scans, signifying a potentially high prevalence of asymptomatic ankle pathology in elite snowboarding athletes. Recognition of these injuries is important to create future strategies for the prevention of long-term sequelae in this high-risk group.